2019
DOI: 10.1002/micr.30499
|View full text |Cite
|
Sign up to set email alerts
|

Lower medial thigh perforator (LMTP) propeller flap for reconstruction of soft tissue defects around the knee

Abstract: Background Skin and soft‐tissue defects around the knee are common and their reconstruction is still challenging and argued. Thin, pliable and well‐vascularized tissues are required in order to restore the aesthetic appearance of the knee and facilitate joint function. Historically local muscle flaps were employed for the upper third of the lower limb reconstruction; however, since their introduction, different perforator flaps have been proposed for this purpose. The aim of this report is to share our clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Coverage of knee defects is still controversial (Table 3). Mohan et al, 2019;Scaglioni et al, 2020) The position of the defect could allow the use of a peroneal perforator flap but this option appeared unreliable in the context of impaired vascularization. (Ruan et al, 2010) No proper ALT or AMT perforators were found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coverage of knee defects is still controversial (Table 3). Mohan et al, 2019;Scaglioni et al, 2020) The position of the defect could allow the use of a peroneal perforator flap but this option appeared unreliable in the context of impaired vascularization. (Ruan et al, 2010) No proper ALT or AMT perforators were found.…”
Section: Discussionmentioning
confidence: 99%
“…(Gravvanis et al, 2005) Fasciocutaneous perforator flaps present the advantages of less morbidity, and better pliability, and cosmetic outcomes. (Gravvanis et al, 2014; Ruan et al, 2010; Scaglioni et al, 2020; Wiedner et al, 2011; Zheng et al, 2015) Many authors recommend the medial sural artery perforator flap (MSAP) in particular (Gstoettner et al, 2019; Ling et al, 2018). Reverse ALT perforator flaps and Reverse Anteromedial Thigh (AMT) perforator flaps are the leading options currently used to reconstruct extensive defects around the knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower medial thigh perforator (LMTP) flap was described by Scaglioni et al in 2015 as a free perforator flap for head and neck reconstruction, and later as a propeller flap for knee reconstruction. 4 We present our experience with six cases, using a free-style approach to the pedicled LMTP flap for reconstruction of knee defects.…”
Section: Introductionmentioning
confidence: 99%